2013
DOI: 10.4103/2278-0513.110802
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of Cauda equina syndrome: Epidural high grade primary non-Hodgkin lymphoma

Abstract: A 55-year-old male presented with progressively increasing low back pain since past 40 days, which worsened on recumbency and sneezing, with recent complaints of urinary incontinence. The patient presented to us 2 weeks after the onset of urinary complaints. His medical history was unremarkable. The patient complained of low back pain with bilateral lower limb radiculopathy with urinary incontinence since 15 days. There was no history of bowel disturbance or weakness of lower limbs. On neurological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The involvement of spinal cord or cauda equina is very rare. The incidence of lymphoma is less than 2% in tumors involving cauda equina [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of spinal cord or cauda equina is very rare. The incidence of lymphoma is less than 2% in tumors involving cauda equina [5].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented to hospital after 1 month of symptoms onset, if he had presented immediately after the symptoms onset the final outcome would have been more favorable. Delay in diagnosis and treatment can lead to devastating outcomes in CES leading to persistent neurologic deficit [5]. In one of the retrospective review of 44 patients with CES it was noted that the delayed surgery group (> 48 h) demonstrated a significantly greater chance of permanent motor weakness, urological dysfunction, chronic severe pain and sexual dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%